Pembuatan nanoekstrak dari kulit buah jeruk kasturi (Citrus microcarpa) dan formulasinya sebagai pasta gigi - Hasibuan , Fika Miah Sasmitha; Dalimunthe, Gabena Indrayani; Lubis , Minda Sari; Rani, Zulmai (Journal of Pharmaceutical and Sciences, 2025)
Dental caries is a common oral health problem among the Indonesian population, and its primary cause is the bacterium Streptococcus mutans. The peel of the Kasturi orange (Citrus microcarpa) fruit has been known to contain antibacterial properties, which may help prevent the occurrence of dental caries. This study aims to evaluate the toothpaste formulation with the active ingredient of nano-extract from kasturi orange peel (Citrus microcarpa). The extract of Kasturi orange peel was obtained through a maceration method, followed by phytochemical screening that identified the presence of flavonoids, steroids, alkaloids, saponins, glycosides, and essential oils. The extract was then processed into a nano-extract, and its particle size was measured using a Particle Size Analyzer (PSA) with a dynamic light scattering technique. The nano-extract was formulated into toothpaste at concentrations of 7.5%, 10%, and 12.5%, and its antibacterial activity was tested. Physical evaluations showed that the toothpaste maintained its shape, color, odor, and taste during storage, was homogeneous, had a pH within the acceptable range (4.5–10.5), viscosity within the required range (20,000–50,000 cps), and passed organoleptic testing (color, aroma, taste, and texture) on respondents.